Sensory information processing in neuroleptic-naive first-episode schizophrenic patients: a functional magnetic resonance imaging study - Braus, Dieter F.; Weber-Fahr, Wolfgang; Tost, Heike; Ruf, Matthias; Henn, Fritz A. (Archives of general psychiatry, 2002)
BACKGROUND: Schizophrenic disorders are thought to involve widespread abnormalities in information processing. The present study used functional magnetic resonance imaging and a simple and robust paradigm that involved auditory and visual activation to examine basic sensory input circuits. Our aim was to determine which stages of the input processing network are disturbed in first-episode schizophrenic patients. - METHODS: Twelve neuroleptic-naive inpatients (paranoid subtype) were compared with 11 healthy subjects by means of echo-planar functional magnetic resonance imaging. In a block design, the paradigm included the simultaneous presentation of a moving 6-Hz checkerboard and auditory stimuli in the form of drumbeats. The subjects were asked to simply look and listen. - RESULTS: In comparison with control subjects, patients showed reduced activation in the right thalamus, the right prefrontal cortex, and the parietal lobe (restricted to the dorsal visual pathway) bilaterally. There were no notable differences in the primary visual cortex or the object-specific occipitotemporal pathway. In addition, patients presented with a reduced signal change to auditory stimulation in the left acoustic cortex. - CONCLUSIONS: The present study supports the concept of widespread cortical and subcortical deficits in schizophrenia. Our findings suggest abnormal functioning early in the information processing and in high-order association cortices already at illness onset, before the administration of medication or the most confounding effects of illness duration. The main regions have been implicated in visual motion perception and discrimination as well as in attention to sensorial events and perceptual synthesis.
Gesehen am 09.11.2.200